Penyuluhan Tentang Kehamilan Dengan 4T Di Wilayah Kerja Puskesmas Ubung - Wardani, Putu Ayu Agustina Eka; Dialuhana; Oktariani, Mega Soli; Natalia, Omiati (CV Putra Publisher, 2025)
Kehamilan dengan faktor risiko